2000
DOI: 10.1080/10913211.2000.10653733
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Financial Characteristics Between Small and Large Firms: An Empirical Examination of the Casino Industry

Abstract: This study examines the differences in financial characteristics between small and large firms in the rapidly expanding casino industry. Financial ratios from 50 casino firms from the fiscal year 1995 are examined to determine the differences between small and large firms. Firms are classified into small and large groups based on the median value of total asset size for sample firms. Wilcox Rank Sum Test, a non-parametric test, is used to test for differences in the financial characteristics of small and large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
(12 reference statements)
0
13
0
Order By: Relevance
“…In our sample, while 41% of the sample firms had dividend payouts, only 13% of casino hotels paid out dividends. Over the past decade (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007), U.S. casino hotels have grown significantly with an average annual revenue growth rate of 12.50% (Upneja et al, 2000;Price Waterhouse Cooppers, 2007). According to a report published by American Gaming Association (2008), U.S. casino industry is offering positive investment opportunities for investors because compliance with regulations and taxation makes the industry's business dealings completely transparent.…”
Section: Conclusion and Suggestions For Future Studiesmentioning
confidence: 98%
“…In our sample, while 41% of the sample firms had dividend payouts, only 13% of casino hotels paid out dividends. Over the past decade (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007), U.S. casino hotels have grown significantly with an average annual revenue growth rate of 12.50% (Upneja et al, 2000;Price Waterhouse Cooppers, 2007). According to a report published by American Gaming Association (2008), U.S. casino industry is offering positive investment opportunities for investors because compliance with regulations and taxation makes the industry's business dealings completely transparent.…”
Section: Conclusion and Suggestions For Future Studiesmentioning
confidence: 98%
“…At the same time, several studies have looked at the effect of firm size on the financial performance and debt of hospitality firms (Dalbor, Kim & Upneja, 2004;Gustin & Kwansa, 1995;Sheel & Wattanasuttiwong, 1998;Upneja, Kim, & Singh, 2000). However, there exists a gap in terms of analyzing the capital structure of lodging firms at different credit availability times.…”
Section: The Journal Of Hospitality Financial Management 35mentioning
confidence: 97%
“…Most of the previous research studies in the area of hospitality firms analyzed the capital structure of lodging firms or the prevalent leverage with other relevant variables (Kim, 1995;Kwansa & Cho, 1995;Nuri & Archer, 2001;Sheel, 1994;Tang & Jang, 2007;Upneja & Dalbor, 2001a, 2001b. At the same time, several studies have looked at the effect of firm size on the financial performance and debt of hospitality firms (Dalbor, Kim & Upneja, 2004;Gustin & Kwansa, 1995;Sheel & Wattanasuttiwong, 1998;Upneja, Kim, & Singh, 2000).…”
Section: The Journal Of Hospitality Financial Management 35mentioning
confidence: 97%
“…Multiple combinations of financial ratios can be developed that can provide valuable financial information. More than a dozen studies were conducted in the U.S. that focused specifically on the utilization of financial ratios in the hospitality industry (e.g., Gu, 2001;Singh, 2001;Upneja, Kim, & Singh, 2000;Singh & Schmidgall, 2001;Ryu & Jang, 2004;Schmidgall & DeFranco, 2004;Kim & Ayoun, 2005). Gu (2001) examined the financial situation of large and small casinos.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study concluded that larger casinos have better liquidity, higher returns on invested capital, and higher returns on average assets in contrast with small casinos. Upneja et al (2000) examined the financial characteristics between small and large casinos. The classification of firms was done based on the median value of total assets for sample firms.…”
Section: Literature Reviewmentioning
confidence: 99%